Stabilitas Hasil Galur Kedelai Toleran Cekaman Kekeringan - Suhartina, Suhartina; Purwantoro, Purwantoro; Nugrahaeni, Novita; Taufiq, Abdullah (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
Soybean in Indonesia mostly is planted on the lowland during dry season. During the season, soybean crops face drought stress at generative phase, that reduces grain yield. Planting of drought tolerance variety is an alternative means to overcome this problem. The objective of this research was to evaluate the adaptability and yield stability of soybean lines tolerant to drought stress. Twelve soybean lines and two check varieties (Wilis and Tidar) were evaluated at eight locations during dry season of 2009 and 2010, planted two times in each location. The treatments were laid out in a randomized complete block design with four replications. These sites were Mojokerto, Banyuwangi, Pasuruan, and Jombang (East Java), Bantul and Sleman (Yogyakarta), Mataram and Lombok Barat (NTB). No irrigation was added during reproductive phase of the crop. Soil moisture content at 0-20 cm soil layer during the generative phase was equivalent to pF value of 3.0-4.2. Analysis of variance over locations and planting seasons showed that there was significant interaction between genotypes and environments. Among the tested-lines, DV/2984-330 was the only line that showed average stability with high grain yield, averaging of 1.95 t/ha out of its yield potential of 2.83 t/ha. This line showed good adaptability over locations with water shortage (20-30% field capacity) during generative phase. Grain yield of this promising line was 14% higher compared to that of Tidar and 16% higher to that of Wilis. This line is prospective to be released as new variety, possessing drought stress during generative phase.